SARS-CoV-2 primed platelets–derived microRNAs enhance NETs formation by extracellular vesicle transmission and TLR7/8 activation - Liao, Tsai-Ling; Liu, Hung-Jen; Chen, Der-Yuan; Tang, Kuo-Tung; Chen, Yi-Ming; Liu, Po-Yu (Cell communication and signaling, 2023)
Hyperactive neutrophil extracellular traps (NETs) formation plays a key role in the pathogenesis of severe COVID-19. Extracellular vesicles (EVs) are vehicles which carry cellular components for intercellular communication. The association between COVID-19 patients-derived EVs and NETs formation remains elusive. We explored the roles of EVs in NETs formation from 40 COVID-19 patients with different disease severities as well as 30 healthy subjects. The EVs-carried microRNAs profile was analyzed using next generation sequencing approach which was validated by quantitative reverse transcription PCR. The regulatory mechanism of EVs on NETs formation was investigated by using an in vitro cell-based assay, including immunofluorescence assay, flow cytometry, and immunoblotting. COVID-19 patient-derived EVs induced NETs formation by endocytosis uptake. SARS-CoV-2 spike protein-triggered NETs formation was significantly enhanced in the presence of platelet-derived EVs (pEVs) and this effect was Toll-like receptor (TLR) 7/8- and NADPH oxidase-dependent. Increased levels of miR-21/let-7b were revealed in EVs from COVID-19 patients and were associated with disease severity. We demonstrated that the spike protein activated platelets directly, followed by the subsequent intracellular miR-21/let-7b upregulation and then were loaded into pEVs. The pEVs-carried miR-21 interacted with TLR7/8 to prime p47phox phosphorylation in neutrophils, resulting in NADPH oxidase activation to promote ROS production and NETs enhancement. In addition, miR-21 modulates NF-ÎºB activation and IL-1[beta]/TNF[alpha]/IL-8 upregulation in neutrophils upon TLR7/8 engagement. The miR-21 inhibitor and TLR8 antagonist could suppress efficiently spike protein-induced NETs formation and pEVs primed NETs enhancement. We identified SARS-CoV-2 triggered platelets-derived GU-enriched miRNAs (e.g., miR-21/let-7b) as a TLR7/8 ligand that could activate neutrophils through EVs transmission. The miR-21-TLR8 axis could be used as a potential predisposing factor or therapeutic target for severe COVID-19.